Toward an ecospheric rhetoric: cleaning up "Trash Isles" - Miller, Jacob A. (Kansas State University, 2019)
To better attune rhetoric to the multiple cascading ecological crises, the recent ecological turn in rhetorical theory has sought to expand the rhetorical situation beyond the human subject, get down and dirty with matter itself, and honor its agential properties. While necessary for pushing the boundaries of rhetorical theory, these various approaches do not adequately express what they mean by the material. “Matter,” “material,” and “object” conceptualizations risk becoming as detached, limitless, and adrift as signifiers of the poststructuralist past, a past new materialists wish to shake. Therefore, an alternative object ontological framework is proposed, called “ecospheric rhetoric.” With this framework, common rhetorical components are re-theorized, such as the parameters of rhetorical situations and the signification process. Ultimately, the purpose of this thesis is to unite ecosphere and rhetoric in a way that makes both sustainable in the long term. This theory serves as the basis for an analysis of the Great Pacific Garbage Patch (GPGP), popularly known as “Trash Isles.” The GPGP is a nearly one million square mile floating patch of trash in the Pacific that contains 79,000 tons of plastic. I argue GPGP represents the material accumulation of the effects of the spatiotemporal rift between the ecosphere as totalizing hyperobject and how it presents itself to us in local manifestations, which calls us to reconceptualize the signification process. The material effects of our discourses are substantially greater than the material effects of the ecosphere relative to the same time frame. Thus, within an ecospheric rhetorical framework the signification process should be reconsidered using a heuristic I coin as “signification weights.” Finally, I discuss implications, limitations, and future research.
Keywords: Trash Isles; Object-oriented ontology; Ecology; Materialism; Great pacific garbage patchEcospheric rhetoric